Application of the Surface Complexation Model to the Biosorption of Cu(II) and Pb(II) Ions onto Biomass - Ruixia Liu; Yonghui Song; Hongxiao Tang (Adsorption Science & Technology)
In this study, a potentiometric titration was performed to investigate the surface acid–base properties of Pseudomonas pseudoalcaligenes isolated from activated sludge. Batch sorption as a function of pH was performed to explain the sorption behaviour of Cu(II) and Pb(II) ions onto the bacterial surface. The surface complexation approach in the frame of constant capacitance model was applied to determine the deprotonation constants, site concentrations and metal stability constants for the important surface-functional groups on the biomass. The optimized results showed that the three discrete sites–three pK a s model, involving three distinct types of functional groups, namely, carboxyl, phosphate and hydroxyl, could actually fit the protonation of the bacterial functional groups, with average pK a values of 4.18, 6.31 and 9.18, and site concentrations of 0.526, 0.525 and 0.478 mmol/g, respectively. The two sites model provided the best fit for the biosorption of Cu(II) and Pb(II) ions onto the biomass by forming complexes with carboxyl and phosphate surface sites, with average log stability constants of 5.95 and 6.94 for Cu(II), and 6.64 and 8.08 for Pb(II), respectively. These results suggested that the surface complexation model yielded the accurate prediction for the biosorption behaviour of Cu(II) and Pb(II) ions on the bacterial biomass and the affinity of P. pseudoalcaligenes biomass for the adsorption of Cu(II) and Pb(II) ions was high enough to remove the metal ions from water.